2013
DOI: 10.1051/alr/2013065
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA and morphological identification ofCrassostrea zhanjiangensissp. nov. (Bivalvia: Ostreidae): a new species in Zhanjiang, China

Abstract: -Cupped oysters (Ostreidae, genus Crassostrea) occupy nearshore marine and estuarine habitats worldwide, providing many ecosystem goods and services as well as being a commercially important group of bivalves. In this study, the species identification of an "adulterant" oyster with small body size, which is often misidentified as a "young individual" of other sympatric species, including C. sikamea and C. hongkongensis, was determined for the first time, based on molecular markers (partial mitochondrial cox1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Furthermore, this method allows accurate species identification of morphologically similar species. DNA barcoding has previously been used to identify a various oyster species as well as newly invasive alien and cryptic species (Banks and Hedgecock 1993;O'Foighil et al 1998;Hedgecock et al 1999;Boundry et al 2003;Lam and Morton 2003;Lapègue et al 2004;Chen et al 2011;Liu et al 2011;Melo et al 2010;Hong et al 2012;Crocetta et al 2013a,b;Gal-Vao et al 2013;Hamaguchi et al 2013;Sekino and Yamashita 2013;Wu et al 2013;Hamaguchi et al 2014;Sekino et al 2014;Xia et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this method allows accurate species identification of morphologically similar species. DNA barcoding has previously been used to identify a various oyster species as well as newly invasive alien and cryptic species (Banks and Hedgecock 1993;O'Foighil et al 1998;Hedgecock et al 1999;Boundry et al 2003;Lam and Morton 2003;Lapègue et al 2004;Chen et al 2011;Liu et al 2011;Melo et al 2010;Hong et al 2012;Crocetta et al 2013a,b;Gal-Vao et al 2013;Hamaguchi et al 2013;Sekino and Yamashita 2013;Wu et al 2013;Hamaguchi et al 2014;Sekino et al 2014;Xia et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the phylogenetic relationship among these four species of oysters, in which C. hongkongensis is the sister group of (C. sikamea, (C. gigas, C. angulata)). [26] To summarize, we have identified 286 proteins from the C. hongkongensis sperm, which form a resource for evolutionary studies of the roles of sperm proteins in fertilization and early development. Since the number and quantity of some reproductive proteins can affect fertilization success and larval development, as demonstrated in fish [27] as well as oysters, [28] our proteomic data will also facilitate further studies aiming to improve oyster stocks in aquaculture.…”
Section: Doi: 101002/pmic202000167mentioning
confidence: 99%
“…Based on the shape of the shell, the oyster is one of the most variable bivalves in the world (Gunter 1950), and therefore, morphology is of limited value for species identification and taxonomy de Melo et al 2010). Crassostrea oysters are widespread and the most commercially important group of oysters, and hence have received more attention concerning their taxonomy, phylogeny and population genetics (Lam and Morton 2003;Reece et al 2008;Liu et al 2011;Li et al 2013;Wu et al 2013). Currently, a total of 35 Crassostrea oysters have been confirmed by professional taxonomists and listed in taxonomic databases such as WoRMS (World Register of Marine Species, http://www.marinespecies.…”
Section: Introductionmentioning
confidence: 99%
“…b Corresponding author: carlzyu@scsio.ac.cn http://www.bagniliggia.it/WMSD/WMSDhome.htm), eoL (Encyclopedia of Life, http://eol.org/) and in Huber (2010); 14 of these species have DNA sequences available in GenBank . Recently, Wu et al (2013) reported a new species (C. zhanjiangensis) in China based primarily on molecular evidence. This Indo-Pacific oyster, previously assumed to be a juvenile of the Kumamoto oyster (C. sikamea) by local farmers, could potentially influence the efficiency of C. hongkongensis spat collection due to niche competition on spat collection devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation